Analysis of the Categories and Strategies of Cross-cultural Conflicts in the operating process of Chinese Multinational Enterprises in the United States - Zhu, Linsen (Archives of Business Research, 2022)
This paper with its focus on Chinese Multinational enterprises operating in the United States has a threefold contribution to the existing literature. First, it summarizes the salient features of the ‘Double Circulation"strategy. Part of it means Chinese enterprises “Going-out” by buying into firms and businesses abroad and by encouraging foreign investment (“Bringing-in”). Second, attention is drawn to importance of understanding the nature and scope of the cultural conflicts that can arise in the trans-cultural organizations that now have to operate in a new and different work culture and work place culture. Third, a typology of cultural dimensions to management are discussed to give the reader a better appreciation of the complexity faced by both Chinese multinational enterprises and the workers who are the subject of a ‘take-over’. By analyzing the cultural differences between China and the United States and the cultural conflicts caused by the trans-cultural organizations, this paper proposes a solution to the cross-cultural communication and management of Chinese multinational companies investing in the United States.